PENGARUH DISIPLIN KERJA, IKLIM KERJASAMA DAN GAYA KEPEMIMPINAN TERHADAP PRESTASI KERJA PEGAWAI PADA KANTOR DINAS PEMADAM KEBAKARAN DIWILAYAH KECAMATAN SEKUPANG DAN BATU AJI, KOTA BATAM - rini elfina (EQUILIBIRIA, 2019)
The results of hypothesis testing show that the three alternative hypothesis (Ha) proposed in thisresearch are accepted, and reject the null hypothesis (H0). Some research conclusions can beformulated as follows:Firstly, there is a significant positive influence of work discipline,cooperative climate, and leadership style on the performance of employees at Fire DepartmentService in Sekupang and Batu Aji Sub-District, Batam City. Thus means the higher the climate ofteamwork the higher the discipline of employee work, the higher the prestai of employee work.Vice versa, the lower the discipline of employee work, the lower the work performance ofemployees. Therefore, work discipline, cooperative climate and leadership style are importantvariables to be considered in improving employee performance At Fire Service Office inSekupang and Batu Aji Sub-District, Batam City.Secondly, there is a significant positiveinfluence Climate cooperation on employee performance At the Fire Department Office inSekupang and Batu Aji Sub-District, Batam City. Thus means the higher the value of teamworkthat highlighted the higher the discipline of employee work, as well as the leadership style thatwill affect the performance of employees in the Office of Fire Department in Sekupang Districtand Batu Aji Batam City. Likewise, on the contrary, the lower the cooperation betweenemployees the lower the employee's performance. Therefore cooperation is an importantvariable to be considered in predicting employee work performance in the future employees.Third, there is a significant positive effect of the cooperation climate on the performance ofemployees at Fire Department Service in Sekupang and Batu Aji Sub-District, Batam City. Thus,the higher the discipline of employees, the higher the employee's performance. Similarly, thelower the discipline of employees, the lower the performance of the pegai. Therefore, disciplineis an important variable to be considered in predicting future work performance.Fourthly, there is a significant positive influence of leadership style on the work performance ofthe Employees at Fire Bureau Office in Sekupang and Batu Aji Sub-District, Batam City. Thus itmeans the better the leadership style, the higher the work performance of the employees at theFire Department Office in Sekupang and Batu Aji areas of Batam City. Similarly, the lower thestyle of leadership that is displayed, the lower the work performance of employees at the FireDepartment Office in Sekupang and Batu Aji areas of Batam City.Keywords: Work Discipline, Climate Cooperation, Leadership Style, Work Achievement